New Sources of Southern Chinch Bug Resistance in St. Augustinegrass - Huangjun Lu; Ronald Cherry (EDIS)
St. Augustinegrass, Stenotaphrum secundatum (Walt.) Kuntze, is widely used for lawns throughout the southern United States and is the predominant turfgrass for lawns in Florida. The southern chinch bug, Blissus insularis Barber, is the plant’s most damaging insect pest. This 4-page fact sheet was written by Huangjun Lu and Ronald Cherry, and published by the UF Department of Horticultural Sciences, July 2014.